Targeting Extracellular Vesicles to the Arthritic Joint Using a Damaged Cartilage-Specific Antibody - Topping, Louise M.; Thomas, Bethan L.; Rhys, Hefin I.; Tremoleda, Jordi L.; Foster, Martyn; Seed, Michael; Voisin, Mathieu-Benoit; Vinci, Chiara; Law, Hannah L.; Perretti, Mauro; Norling, Lucy V.; Azevedo, Helena S.; et al. (Frontiers in Immunology, 2020)
The targeted delivery of therapies to diseased tissues offers a safe opportunity to achieve optimal efficacy whilst limiting systemic exposure. These considerations apply to many disease indications, but are especially relevant for rheumatoid arthritis (RA), as RA is a systemic autoimmune disease which affects multiple joints. We have identified an antibody that is specific to damaged arthritic cartilage (anti-ROS-CII) that can be used to deliver treatments specifically to arthritic joints, yielding augmented efficacy in experimental arthritis. In the current study, we demonstrate that scaffold enriched with bioactive payloads can be delivered precisely to an inflamed joint and achieve superior efficacy outcomes consistent with the pharmacological properties of these payloads. As a scaffold, we have used extracellular vesicles (EV) prepared from human neutrophils (PMN), which possess intrinsic anti-inflammatory properties and the ability to penetrate inflamed arthritic cartilage. EV fortified with anti-ROS-CII (EV/anti-ROS-CII) retained anti-ROS-CII specificity and bound exclusively to the damaged cartilage. Following systemic administration EV/anti-ROS-CII: a) exhibited the ability to localise specifically in the arthritic joint in vivo and b) was able to specifically target single (viral IL-10 or anti-TNF) or combined (viral IL-10 and anti-TNF) anti-inflammatory treatments to the arthritic joint, which accelerated attenuation of clinical and synovial inflammation. Overall, this study demonstrates the attainability of targeting a pro-resolving biological scaffold to the arthritic joint. The potential of targeting scaffolds such as EV, nanoparticles or combination thereof alongside combined therapeutics is paramount for designing systemically administered broad-spectrum of anti-inflammatory treatments.